Modern Animal Nicknames of Foreign Origin (Linguostylistic Studies, 2016)
The article considers modern tendencies in giving names to the domestic animals. The author claims that for centuries there has been generated a large group of traditional nicknames given to the domestic animals (cow Lyska, horse Gnidko, dog Zhuchyk and others). But in the second half of the twentieth century under the influence of literature, cinema and television films there appeared many new zoonyms. Another reason for such modifications is the fact that modernized names of the newborn animals are usually chosen by representatives of the younger and the youngest generations, which is evidenced in quite specific zoonyms, in which slang words are used for the formation of the new names (cf.: dogs Drushban, Cora, Tina, Shavka, Sheva; cat – Pakhan (even the dog obeys him) and others). Among the newly created nicknames a significant percentage of words are of foreign origin, including rosiizmy (e.g. cow nicknames: Aprielka, Kukla, Nieviesta). Some animal nicknames are of English and American origin. In the majority of them nominative nouns and their derivatives are used as name-forming stems (dogs – Boi, Blek, Dog, Frend, phelihonyms Dzhek, Oliver, Dzhulia and others). Key words: north-western Ukraine, nicknames of animals, honyms, anthroponyms, appellatives. References